2015
DOI: 10.1039/c5ra10317g
|View full text |Cite
|
Sign up to set email alerts
|

Facile iron(iii)-mediated ATRP of MMA with phosphorus-containing ligands in the absence of any additional initiators

Abstract: A series of phosphorus-containing ligands was employed to establish a novel polymerization system for the iron(III)-mediated polymerization of methyl methacrylate (MMA) just using FeCl 3 $6H 2 O or FeBr 3 as the catalyst without any additional initiators and reducing agents. The polymerization results showed that this polymerization system involving MMA/FeX 3 (X ¼ Cl, Br)/phosphorus-containing ligand was a typical "living"/controlled radical polymerization process: first-order polymerization kinetics with resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…The controlled/"living" characteristics are conrmed by a measured molecular weight value close to the theoretical one and a low PDI value. These ndings are in agreement with the results of Bai et al 58 In particular, as clearly demonstrated by Table 1, with an optimized molar ratio of 2 : 2 (entry 2) the IL may readily coordinate to FeCl 3 . With large amount of IL, with a molar ratio of 2 : 40 (entry 1), the FeCl 3 /IL complex could be preferentially destroyed, while with a FeCl 3 /IL molar ratio of 2 : 1, free FeCl 3 metal compound could potentially retard or inhibit the radical polymerization of MMA (entry 3).…”
Section: With a Further Decrease In [C 12 Mim][cl] 0 To A Ratio Of [Fsupporting
confidence: 92%
“…The controlled/"living" characteristics are conrmed by a measured molecular weight value close to the theoretical one and a low PDI value. These ndings are in agreement with the results of Bai et al 58 In particular, as clearly demonstrated by Table 1, with an optimized molar ratio of 2 : 2 (entry 2) the IL may readily coordinate to FeCl 3 . With large amount of IL, with a molar ratio of 2 : 40 (entry 1), the FeCl 3 /IL complex could be preferentially destroyed, while with a FeCl 3 /IL molar ratio of 2 : 1, free FeCl 3 metal compound could potentially retard or inhibit the radical polymerization of MMA (entry 3).…”
Section: With a Further Decrease In [C 12 Mim][cl] 0 To A Ratio Of [Fsupporting
confidence: 92%
“…Besides, an Fe­(III)-based ATRP using phosphorus ligands without any radical initiator [e.g., 2,2′-azobis­(isobutyronitrile) (AIBN)] and reducing agent was reported by Noh and co-workers, in which the authors proposed that the Fe­(III) deactivator was reduced by methyl methacrylate at 80 °C. It should be noted that 2 equiv of phosphorus ligand was required for the catalyst coordination in these work. Nevertheless, an additional mechanism insight given by Matyjaszewski and co-wokers recently showed that phosphines play a dual role as reducing agents and ligand for Fe­(III) salt in this system. , Additionally, Noh and co-workers and Bai and co-workers reported a similar iron­(III)-based polymerization system in the absence of any additional initiators (i.e., no radical initiator or alkyl halides initiator) under high temperature. However, different underlying mechanisms were proposed by these groups.…”
Section: Introductionmentioning
confidence: 90%
“…In recent years, transition-metal complexes in a higher oxidation state or/and parts per million (ppm) catalyst loading was required in newly developed ATRP methods. , These approaches can be divided into two types by the method of continuously regenerating activators: one is a chemical method and the other is a physical method. As to the former, for example, the activators in reverse ATRP, activators generated by electron transfer (AGET) ATRP, activators regenerated by electron transfer (ARGET) ATRP, , initiators for continuous activator regeneration (ICAR) ATRP, and supplemental activators and reducing agent (SARA) ATRP were continuously regenerated through using conventional radical initiator or organic–inorganic reducing agents. Besides, an Fe­(III)-based ATRP using phosphorus ligands without any radical initiator [e.g., 2,2′-azobis­(isobutyronitrile) (AIBN)] and reducing agent was reported by Noh and co-workers, in which the authors proposed that the Fe­(III) deactivator was reduced by methyl methacrylate at 80 °C. It should be noted that 2 equiv of phosphorus ligand was required for the catalyst coordination in these work.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies such as supplemental activator and reducing agent (SARA) ATRP (also termed single electron transfer living radical polymerization, SET‐LRP), 3 initiators for continuous activator regeneration (ICAR) ATRP, 4 activator regeneration by electron transfer (ARGET) ATRP, 5 electrochemically mediated polymerization (eATRP), 6 mechanochemically mediated polymerization (mechanoATRP) 7 and photochemically mediated procedures (photoATRP) 8 have been developed for the controlled synthesis of functional polymers. In most strategies, transition metals, such as copper, 9 iron, 10 ruthenium 11 etc., can efficiently promote the ATRP process of vinyl monomers via an activation/deactivation cycle between the predominant dormant species and a low concentration of propagating radicals, and revealed excellent control on the polymerization procedure. But left problem of metal pollutant, that only ppm level of catalyst residue in the polymer products can greatly influence their performance in electronic or biomaterial applications.…”
Section: Introductionmentioning
confidence: 99%